STRATEGI KEPALA SEKOLAH DALAM IMPLEMENTASI PENDIDIKAN NILAI DI SEKOLAH - Achmad Rifai (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2018)
Globalization is an era marked by the rapid development of science and technology, so it can change the world fundamentally. Globalization era knows no geographical boundaries between countries are due to the limit is no longer able to stem the distribution of information that is increasingly diverse. One of the negative impacts of the globalization era is the shifting of local values (cultural) and religious values. Through globalization, various ideologies that conflict with local and religious values have affected some of mankind. Seeing the various realities, there must be concrete steps to overcome them. One is to maximize value education in schools so as to have a positive impact on the behaviour of learners inside and outside of school. The headmaster as a leader in school has a very important role. The strategy used by a headmaster in implementing values education in schools affect his level of understanding and practice. Especially influence on the level of awareness of students in the practice of noble values, both of which are in institutions or outside the institution, whether formal or non-formal. The use of the right strategy will produce value as desired.